Using an appetitive operant conditioning paradigm to screen rats for tinnitus induced by intense sound exposure: Experimental considerations and interpretation - Hayes, Sarah H.; Beh, Krystal; Typlt, Marei; Schormans, Ashley L.; Stolzberg, Daniel; Allman, Brian L. (Frontiers in Neuroscience, 2023)
In an effort to help elucidate the neural mechanisms underlying tinnitus in humans, researchers have often relied on animal models; a preclinical approach which ultimately required that behavioral paradigms be designed to reliably screen animals for tinnitus. Previously, we developed a two-alternative forced-choice (2AFC) paradigm for rats that allowed for the simultaneous recording of neural activity at the very moments when they were reporting the presence/absence of tinnitus. Because we first validated our paradigm in rats experiencing transient tinnitus following a high-dose of sodium salicylate, the present study now sought to evaluate its utility to screen for tinnitus caused by intense sound exposure; a common tinnitus-inducer in humans. More specifically, through a series of experimental protocols, we aimed to (1) conduct sham experiments to ensure that the paradigm was able to correctly classify control rats as not having tinnitus, (2) confirm the time course over which the behavioral testing could reliably be performed post-exposure to assess chronic tinnitus, and (3) determine if the paradigm was sensitive to the variable outcomes often observed after intense sound exposure (e.g., hearing loss with our without tinnitus). Ultimately, in accordance with our predictions, the 2AFC paradigm was indeed resistant to false-positive screening of rats for intense sound-induced tinnitus, and it was able to reveal variable tinnitus and hearing loss profiles in individual rats following intense sound exposure. Taken together, the present study documents the utility of our appetitive operant conditioning paradigm to assess acute and chronic sound-induced tinnitus in rats. Finally, based on our findings, we discuss important experimental considerations that will help ensure that our paradigm is able to provide a suitable platform for future investigations into the neural basis of tinnitus.